Feasibility of optical diffraction radiation for a non-invasive low-emittance beam diagnostics; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 472, iss. 1-2 - Urakawa J.; Hayano H.; Kubo K.; Kuroda S.; Terunuma N.; Kuriki M.; Okugi T.; Naito T.; Araki S.; Potylitsyn A. P. Alexander Petrovich; Naumenko G. A. Gennadiy Andreevich; Karataev P.; et al. (2001, 2001)
Title screen